2019
DOI: 10.1021/acsnano.9b05659
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatically Doped Silicon Nanowire Arrays for Multispectral Photodetectors

Abstract: Nanowires have promising applications as photodetectors with superior ability to tune absorption with morphology. Despite their high optical absorption, the quantum efficiencies of these nanowire photodetectors remain low due to difficulties in fabricating a shallow junction using traditional doping methods. As an alternative, we report nonconventional radial heterojunction photodiodes obtained by conformal coating of an indium oxide layer on silicon nanowire arrays. The indium oxide layer has a high work func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 47 publications
0
32
0
2
Order By: Relevance
“…Since in this case, the intrinsic absorption constitutes the main reason for the photon energy loss, 30 the majority of incident UV photons will be absorbed by the SiNWs, which might be beneficial for UV light detection. It should be noted that, while a number of research groups have reported various SiNW arrays that exhibit tailorable absorption in the NIR and visible light regions, 31,32 we have successfully reported experimentally SiNW arrays whose peak absorption can be tuned from the NIR to UV light regions by engineering the diameter. This finding is interesting and can be attributed to the PS assisted etching method, which can achieve very good anisotropic Si etching with aspect ratios as high as 100.…”
Section: Resultsmentioning
confidence: 89%
“…Since in this case, the intrinsic absorption constitutes the main reason for the photon energy loss, 30 the majority of incident UV photons will be absorbed by the SiNWs, which might be beneficial for UV light detection. It should be noted that, while a number of research groups have reported various SiNW arrays that exhibit tailorable absorption in the NIR and visible light regions, 31,32 we have successfully reported experimentally SiNW arrays whose peak absorption can be tuned from the NIR to UV light regions by engineering the diameter. This finding is interesting and can be attributed to the PS assisted etching method, which can achieve very good anisotropic Si etching with aspect ratios as high as 100.…”
Section: Resultsmentioning
confidence: 89%
“…The ease of bandgap conversion from indirect to direct band due to dimension, crystallography, mechanical strain, and alloying allows SiNWs to be used in the optical applications—e.g., photodetectors (PDs) and light emitters (LEs). Since silicon nanowires have a superior ability to tune absorption with morphology, Um et al reported that SiNWs with a coating of an indium oxide layer on it, lead to efficient carrier separation and collection, resulting in an improvement of quantum efficiency and by controlling the nanowire radii, can create a multispectral detector [ 229 ].…”
Section: Applicationsmentioning
confidence: 99%
“…Semiconductor nanowires (NWs) show high light sensitivity due to the large surface area to volume ratio, as well as high photoconductive gain due to surface state promoted charge separation. Silicon is one of the most common visible light photoconductive materials due to its common use in electronics [2] and the resulting highly developed fabrication technology [4][5][6][7]. When silicon-based nanoscale photodetection devices perform in the near field of the observed object, they are disturbed by noise introduced due to light scattered by the sensor itself [2,8,9].…”
Section: Introductionmentioning
confidence: 99%